Spermine and Spermidine Alter Gene Expression and Antigenic Profile of Borrelia burgdorferi - Lin, Ying-Han (Infect Immun, 2017)
Borrelia burgdorferi, the agent of Lyme disease, responds to numerous host-derived signals to alter adaptive capabilities during its enzootic cycle in an arthropod vector and mammalian host. Molecular mechanisms that enable B. burgdorferi to detect, channel, and respond to these signals have become an intense area of study for developing strategies to limit transmission/infection. Bioinformatic analysis of the borrelial genome revealed the presence of polyamine transport components (PotA, PotB, PotC, and PotD), while homologs for polyamine biosynthesis were conspicuously absent. Although potABCD is cotranscribed, the level of PotA was elevated under in vitro growth conditions mimicking unfed ticks compared to the level in fed ticks, while the levels of PotD were similar under the aforementioned conditions in B. burgdorferi. Among several polyamines and polyamine precursors, supplementation of spermine or spermidine in the borrelial growth medium induced synthesis of major regulators of gene expression in B. burgdorferi, such as RpoS and BosR, with a concomitant increase in proteins that contribute to colonization and survival of B. burgdorferi in the mammalian host. Short transcripts of rpoS were elevated in response to spermidine, which was correlated with increased protein levels of RpoS. Transcriptional analysis of rpoZ and B. burgdorferi rel (rel(Bbu); bb0198) in the presence of spermidine revealed the interplay of multiple regulatory factors in B. burgdorferi gene expression. The effect of spermidine on the levels of select borrelial proteins was also influenced by serum factors. These studies suggest that multiple host-derived signals/nutrients and their transport systems contribute to B. burgdorferi adaptation during the vector and vertebrate host phases of infection.